Advancing Teams Research: What, When, and How to Measure Team Dynamics Over Time - Delice, Fabrice; Rousseau, Moira; Feitosa, Jennifer (Frontiers in Psychology, 2019)
Teams are considered to be extremely complex dynamic entities that suffer at the hand of constant evolution of their structure to meet and adapt to the varying situational demands they come face-to-face with (Kozlowski & Ilgen, 2006). Agencies, industries, and government institutions are currently placing greater attention to the adaption of team dynamics and teamwork as they are important to key organizational outcomes. As greater attention is being placed on the maturation of team dynamics, the incorporation of efficient methodological tools to understand how teams are being measured over time becomes critical. Thus, the purpose of this paper is to present a review of relevant academic articles detailing the science behind methodological tools and general approaches to study team dynamics over time. We provide an overview of the methodological tools used to understand team dynamics with accordance to specific temporal elements. Drawing from Kozloski, Gully, Nason, and Smith (1999) process model of team development, we highlight relevant emergent team constructs within each stage. As well, for each stage, we discuss the what and how to measure team dynamics. Our analyses bring to light relevant, novel and complex approaches being used by researchers to examine specific constructs within different team developmental phases (e.g., agent-based simulations, computational modeling) and the importance of transitioning from a single source methodology approach. Implications and future research are also discussed.